Unsung helpers: older adults as a source of digital media support for their peers. Issue 4 (1st October 2020) - Hunsaker, Amanda; Nguyen, Minh Hao; Fuchs, Jaelle; Karaoglu, Gökçe; Djukaric, Teodora; Hargittai, Eszter
ABSTRACT: While the stereotypical older adult is one who is clueless about technology, research on this age group paints a different picture. Adding to the literature about older adults' varying tech savvy, this paper focuses on the technological support-giving abilities of those in later stages of life based on interviews conducted in four countries. Far from being dependent bystanders, some older adults serve as helpful sources of support to their peers. We also find mutual support – support given to each other – an important domain for how people in this age group give and get assistance when they encounter technical problems. That such a prominent amount of support providers exist in this age group implies that peer-led technical support approaches may be especially salient and effective in helping older adults use digital media. While some participants did not provide help with digital technology because they lacked confidence to do so, others believed they could, but were never asked. These individuals have the potential to play a critical role in digital media support that may be more acceptable to their peers than help from other age groups. Further investigation of how to harness this support is warranted.